Evidence for unnatural-parity contributions to electron-impact ionization of laser-aligned atoms - Armstrong, G. S. J.; Colgan, J.; Pindzola, M. S.; Amami, S.; Madison, D. H.; Pursehouse, J.; Nixon, K. L.; Murray, A. J. (My University, 2015)
Recent measurements have examined the electron-impact ionization of excited-state laser-aligned Mg atoms. In this work we show that the ionization cross section arising from the geometry where the aligned atom is perpendicular to the scattering plane directly probes the unnatural parity contributions to the ionization amplitude. The contributions from natural parity partial waves cancel exactly in this geometry. Our calculations resolve the discrepancy between the nonzero measured cross sections in this plane and the zero cross section predicted by distorted-wave approaches. We demonstrate that this is a general feature of ionization from p-state targets by additional studies of ionization from excited Ca and Na atoms.